Axial and lateral resistance coupling in the analysis of large-diameter drilled shafts. (1st March 2020) - Taghavi, Amirata; McVay, Michael; Niraula, Lila; Davidson, Michael; Patil, Anand
Highlights: An approach is proposed in a BNWF framework to analyze large-diameter drilled shafts. The approach considers the coupling between axial and lateral resistance through m-θ springs. Results from coupled analyses are validated against centrifuge and full-scale load tests. Conducting a coupled analysis can result in a more economical design. Geomaterial property at shallow depth, shaft diameter, and length are driving factors for coupled analysis. Abstract: Pier foundations subjected to lateral loads are commonly designed using beam on nonlinear Winkler foundation (BNWF) models. This form of soil-structure interaction (SSI) modeling typically involves load transfer between structural members (e.g., drilled shafts) and surrounding soil via nonlinear soil resistance springs, which are distributed along the centerline of beam-column elements. Physically, soil resistance develops at the shaft-soil interface, and special considerations may be warranted regarding coupling between axial and lateral resistance when modeling large-diameter drilled shafts. Presented in this paper are side (t-z) and lateral (p-y) soil-resistance relationships for Florida limestone, obtained from centrifuge tests, and moment-rotation springs associated with coupling of axial and lateral resistances of laterally loaded drilled shafts. Using the coupled approach, BNWF models are developed that: 1) Capture physically measured lateral load responses of shafts founded in a range of soil/rock types; and, 2) Are suitable for large-diameter shafts at variable embedment lengths. This study highlights the need for such analyses in cases when relatively stiff soil/rock materials exist at shallow depths and/or when shafts undergo significant rotations. Use of coupled analysis is found to reduce computed maximum values of shaft bending moment and deflection up to 12% and 19%, respectively, compared to uncoupled analysis.